Education and Empowerment of Human Resources in Efforts to Manage the Environment Towards Green Villages in Dataran Tinggi Village - Nasution, Lisda Rimayani; Sembiring, Riky Cristian; Charlos Samule; Enda Sendari; Rizky Anugrah Putra; Zukhrina Az Zukhruf (Talenta Publisher, 2023)
Dataran Tinggi Village is one of the villages located in the administrative area of East Binjai District, Binjai City. Dataran Tinggi Village has a population of 6,789 people in 2021 which occupies an area of 42.6 H. Based on the results of interviews conducted with the Head of the Dataran Tinggi Village stated that most people have a bad habit of burning garbage. For this reason, activities are needed that can reduce the habits of these people. Implementation methods used are lectures and demonstrations. The dedication activity was attended by 73 participants. The details of the participants included 25 participants in waste management socialization, 18 participants in making verticulture, and 30 participants in socializing waste management into compost. The series of activities carried out included socialization on waste management to elementary school children, socialization on processing waste into compost using the takakura and vermicompost methods, and making verticulture. The results of the implementation of the activity were in the form of increasing students' knowledge related to waste management by 76%, compost, and 3 series of vertical pipes. It can be concluded that real work lecture activities are able to increase human resources and reduce people's habit of burning garbage.